Psychometric properties of the Persian version of the "Intergenerational relationship quality scale for aging parents and their children" - Maryam Torabian; Reza Fadayevatan; Nasibeh Zanjari; Mahshid Foroughan; Gholamreza Ghaedamini Harouni (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Investigating the status of intergenerational relationships of elderly parents with their adult childen is very important in examining issues related to the status of the elderly such as well being and quality of life and other aspects of elderly life. Giveeen the significance of the topic, the current study aimed to examine the psychometric properties of the Persian version of "Intergenerational Relationship Quality Scale for Aging Parents and Their Children" (IRQS-AP). MATERIALS AND METHODS: A total of 463 community-dwelling elders (aged 60 years or older) in Tehran participated in this study through multistage cluster sampling method. To investigate reliability, the construct and convergent validity of the IRQS-AP, confirmatory factor analysis (CFA), and interclass correlation coefficient were done. RESULTS: The content validity index was 0.84 for the entire tool. In the CFA, we found the instrument had a four-factor structure and adequate internal consistency. The scale had a significant and positive correlation with the two measures of loneliness and depression. Furthermore, Cronbach's alpha was estimated at 0.77, and the high value of the interclass correlation was 0.82. CONCLUSION: The IRQS-AP is a valid and reliable scale that can be used to examine the status of intergenerational relationship quality in Iranian elder population.